Study on the Vibration Characteristic and Modal Analysis of Automobile Transmission Shell - Wu Wenxuan; Zhang Jiping; Ma Weijin; Wang Junyuan (Jixie chuandong)
A type of automobile gearbox has box cracking problem,in order to make a structure optimization and precise modal analysis of the automobile transmission shell,with this type of automobile transmission shell as the research object,the automobile characteristics are studied,the optimal excitation direction and frequency band of the dynamic response of the gearbox are obtained,understanding of the inherent characteristics of the transmission shell. Then,by combining the finite element analysis and experimental modal analysis,the modal analysis of automobile transmission shell is carried out,after comparing the obtained data,the reasons for cracking of the transmission shell are analyzed,the foundation for the follow-up of the structural optimization of this type automobile transmission is established.